Do the Powerful Discount the Future Less? The Effects of Power on Temporal Discounting - Duan, Jinyun; Wu, Sherry J.; Sun, Luying (Frontiers in Psychology, 2017)
Individuals have the tendency to discount rewards in the future, known as temporal discounting, and we find that sense of power (the felt capacity to influence the thinking and behavior of others) reduces such tendency. In Studies 1 and 2, we used both an experiment and a survey with organizational employees to demonstrate that power reduced temporal discounting. In Study 3, we replicated study 1 while exploring a unique cultural trait of Danbo, or indifference to fame and wealth, across two ethnic groups (Han and Tibetan groups) in China. While power reduces temporal discounting, the relationship between the two may be leveraged by individual differences of optimism, frustration, and Danbo. The results imply a more nuanced interpretation of how individual and situational factors can affect intertemporal choice.